EFEKTIVITAS PELAKSANAAN PROGRAM USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) FAJAR KEHIDUPAN DI KELURAHAN MUARA FAJAR KECAMATAN RUMBAI KOTA PEKANBARU - Seprianis "; Meizy Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Village Empowerment Program (VEP) is a government program toovercome problems of poverty, one of which is trough the Village EconomicEnterprise Savings and Loan/UEK-SP. The program aims to empower thecommunity that is by providing loan funds to communicaties to develope theirbusiness purpose, but for activities that are consumtive so that ensue the arrearsoccured in loan repayment program save business from the program UEK-SP.And impartial adminstration of funds to the poor so that the core objectives of theprogram is not reached. As for the theory used in this research is effectiveness ofthe implementation of policy according to Goggin, et all. The result of thisresearch indicate yet effectively implementing programs Village EconomicEnterprise Saving and Loan/UEK-SP in the Muara Fajar village District RumbaiPekanbaru city. This can be understood because not done well despite the currentreturn, but given the business loan is not growing. Here the procces ofsocialization and verification has not run optimally, given the funds that is notused properly for business activity and that so the purpose of UEK-SP has notbeen achieved. Factors that influence the implementation of program UEK-SPFajar Kehidupan are : humanKeywords : Effectiveness, Usaha Ekonomi Kelurahan Simpan Pinjam (UEKSP).esources, community economic factors, communication and controlling.